1998
DOI: 10.1246/cl.1998.1143
|View full text |Cite
|
Sign up to set email alerts
|

Direct Hydrogenation of Carboxylic Acids to Corresponding Aldehydes Catalyzed by Palladium Complexes in the Presence of Pivalic Anhydride

Abstract: Carboxylic acids are catalytically hydrogenated into corresponding aldehydes by palladium complexes in the presence of pivalic (trimethylacetic) anhydride under H2. Less hindered aliphatic and aromatic acids are reduced to aldehydes in high yields. The method is also applicable to hydrogenation of dibasic carboxylic acids and carboxylic acids containing heterocyclic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(16 citation statements)
references
References 5 publications
1
14
0
1
Order By: Relevance
“…However, aldehyde productivity is limited to 50% by the reaction mechanism that involves hydrogenolysis of Pd-acyl and Pdcarboxylato groups in [Pd(PPh 3 ) 2 (C(O)R)(O 2 CR)] to give an equal mixture of aldehydes and acids [105]. Very bulky anhydrides were significantly more difficult to reduce, which led this group to design a process for converting carboxylic acids into aldehydes in the presence of bulky anhydrides [105][106][107]. Thus, heating a wide range of less sterically demanding acids in the presence of The reaction tolerates ketone, chloride, internal C=C bonds, esters, nitriles, and ether functional groups.…”
mentioning
confidence: 99%
“…However, aldehyde productivity is limited to 50% by the reaction mechanism that involves hydrogenolysis of Pd-acyl and Pdcarboxylato groups in [Pd(PPh 3 ) 2 (C(O)R)(O 2 CR)] to give an equal mixture of aldehydes and acids [105]. Very bulky anhydrides were significantly more difficult to reduce, which led this group to design a process for converting carboxylic acids into aldehydes in the presence of bulky anhydrides [105][106][107]. Thus, heating a wide range of less sterically demanding acids in the presence of The reaction tolerates ketone, chloride, internal C=C bonds, esters, nitriles, and ether functional groups.…”
mentioning
confidence: 99%
“…46 We also noted that carboxylic anhydrides having relatively bulky substituents undergo the catalytic hydrogenation much more slowly than the less sterically hindered anhydrides. 46 We also noted that carboxylic anhydrides having relatively bulky substituents undergo the catalytic hydrogenation much more slowly than the less sterically hindered anhydrides.…”
Section: Equation 15mentioning
confidence: 72%
“…Through our studies on the comparative reactivities of various carboxylic anhydrides with Pd 0 complexes, we found that carboxylic anhydride such as 2,2dimethylpropionic anhydride (pivalic anhydride) proved to be much less reactive than the less-bulky carboxylic anhydrides [34] [35]. Prompted by this finding, we designed a catalytic system with pivalic anhydride added to the system containing the carboxylic acid to be hydrogenated.…”
Section: 2mentioning
confidence: 99%